Mantle cell lymphoma in the orbital and adnexal region. Issue 8 (7th May 2009) - Rasmussen, P; Sjö, L D; Prause, J U; Ralfkiaer, E; Heegaard, S
Abstract : Aims: To characterise clinicopathological features of mantle cell lymphoma (MCL) in the orbital and adnexal region. Methods: Data on lymphoid lesions were retrieved searching the Danish Ocular Lymphoma Database 1980–2005. Specimens were collected from Danish pathological departments and re-evaluated with a panel of monoclonal antibodies. For all patients with confirmed MCL the complete clinical files were collected and reviewed. Results: Twenty-one patients with MCL in the orbital and adnexal region were identified comprising 9% (21/230) of all lymphoma in the ocular region. There were 18 male patients and three female patients with an age range from 60 to 90 years (median 75 years). Orbital and adnexal region MCL as first presenting symptom comprised 67% of the patients. Of these, 71% had bilateral involvement. The orbit (71%) and eyelids (64%) were the most commonly affected sites. All but two presented in stage III/IV. Secondary MCL comprised 33% of the patients. Bilateral affection (29%) was less common in this patient group. The median survival was not different between the two presentation groups. Patients receiving anti-CD20 (rituximab)-containing chemotherapy had a significantly better 5-year overall survival (OS) rate (83%) than patients in treatment regimes without rituximab (5-year OS rate, 8%). Conclusions: Orbital and adnexal region MCL presents in elderly males. The orbit and eyelid are frequently involved. There is a very high proportion of systemic involvement in general with MCL of the orbital and adnexal region. Most patients presented with stage IV disease and had multiple relapses and short survival time. Treatment with rituximab-containing chemotherapy improved survival significantly compared with combination chemotherapy without rituximab.